2017
DOI: 10.3892/ijmm.2017.3319
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-137 regulates hypoxia-induced retinal ganglion cell apoptosis through Notch1

Abstract: The apoptosis of retinal ganglion cells (RGCs) is a hallmark of several optic neuropathies. MicroRNAs (miRNAs) are recently identified regulators of various biological processes. However, the role of miRNAs in regulating RGC apoptosis remains largely unknown. We herein aimed to demonstrate that miR-137 acts as a hypoxia-responsive gene in RGCs that is downregulated under hypoxic conditions. It was observed that overexpression of miR-137 markedly aggravated hypoxia-induced cell apoptosis, whereas inhibition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…The results of the present study suggested that the activation of the Notch signaling pathway serves a pivotal role in HG-mediated HRECs injury. In retinal ganglion cells, hypoxia-induced Notch1 expression and signaling activation, and inhibition of Notch signaling significantly aggravated hypoxia-induced cell apoptosis (40). In a co-culture system of ligand-dependent Notch activation using primary cultured retinal pericytes and a mesenchymal cell line derived from an inducible mouse model expressing δ-like 1 Notch ligand, ligand-mediated Notch activity was observed to protect retinal pericytes from light-induced cell death (41).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study suggested that the activation of the Notch signaling pathway serves a pivotal role in HG-mediated HRECs injury. In retinal ganglion cells, hypoxia-induced Notch1 expression and signaling activation, and inhibition of Notch signaling significantly aggravated hypoxia-induced cell apoptosis (40). In a co-culture system of ligand-dependent Notch activation using primary cultured retinal pericytes and a mesenchymal cell line derived from an inducible mouse model expressing δ-like 1 Notch ligand, ligand-mediated Notch activity was observed to protect retinal pericytes from light-induced cell death (41).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that miR-137 could directly target on Notch1 and participate in diabetic kidney disease [35], ischemic stroke [36], and hypoxia-induced retinal ganglion cell apoptosis [37]. Our finding indicated that silence of DSCAM-AS1 and miR-137 mimics could suppress Notch-1 signaling, which is a novel pathway regulating cell proliferation and EMT.…”
Section: Discussionmentioning
confidence: 50%
“…Though it is still debatable whether NOTCH signal plays a positive or negative role in osteogenesis [55], our data displayed impaired osteogenic capacity of hASCs after knocking down NOTCH1. More strikingly, NOTCH1 was validated as a direct target gene of miR-137 in hASCs, the same as in other cell lines [40][41][42][43][44]. HES1 is known as a potential downstream target of NOTCH1 in many studies, but it is not affected in NOTCH1 knockout mice while the expression of HES5, HES-related repressor protein (HERP)1, -2, and − 3 are greatly diminished [56][57][58].…”
Section: Discussionmentioning
confidence: 92%
“…HES1 inactivation not only increases the femoral length and trabecular number in the limb bud of transgenic mice, but also enhances mineral apposition rate and suppresses bone resorption in osteoblasts [39]. NOTCH1 has emerged as a target of miR-137 in human renal mesangial cells [40], retinal ganglion cells [41], neurons [42], non-small cell lung cancer cells [43] and breast cancer cells [44], but whether it is directly inhibited by miR-137 has not yet been identi ed in hASCs. In small cell lung cancer cells, NOTCH1 pathway is activated by LSD1 inhibitor and suppressed due to the binding of LSD1 [45].…”
mentioning
confidence: 99%